Pre‐Dialysis Neutrophil‐Lymphocyte Ratio, a Novel and Strong Short‐Term Predictor of All‐Cause Mortality in Patients With Diabetic Nephropathy: Results From a Single‐Center Study. Issue 4 (30th June 2017) - Sato, Hiroyuki; Takeuchi, Yoichi; Matsuda, Ken; Kagaya, Saeko; Saito, Ayako; Fukami, Hirotaka; Ojima, Yoshie; Nagasawa, Tasuku
Abstract: Neutrophil‐lymphocyte ratio (NLR) is an inflammatory marker affecting the prognosis of end‐stage renal disease (ESRD) patients. This study aimed to evaluate NLR levels predicting all‐cause mortality in ESRD patients with diabetic nephropathy (DN), which have not been evaluated. We recruited 151 isolated DN patients who started hemodialysis between January 2009 and December 2014 at the Japanese Red Cross Ishinomaki Hospital. The primary outcomes were 1‐ and 3‐year survival rates. The association between NLR and survival rate was evaluated using the Kaplan–Meier method and Cox proportional hazard regression analysis. Patients with an NLR ≥ 3.5 had a significantly higher mortality rate than did those with an NLR < 3.5 (log rank P =  0.02). The area under the curve (AUC) of 1‐year survival for NLR was significantly larger than that for other commonly used nutritional and inflammatory variables. NLR was a more accurate predictor than other well‐known markers.